Circular Abscess Formation of the Inner Preputial Leaf as a Complication of a Penile Mondor's Disease: The First Case Report. (27th April 2014) - Wendler, Johann Jakob; Schindele, Daniel; Baumunk, Daniel; Liehr, Uwe-Bernd; Porsch, Markus; Schostak, Martin
Abstract : Introduction. Mondor's disease of the penis is an uncommon condition characterized by thrombosis or thrombophlebitis involving the superficial dorsal veins. An accompanied lymphangitis is discussed. There is typical self-limiting clinical course. Case Presentation. This paper firstly reports a secondary abscess formation of the preputial leaf two weeks after penile Mondor's disease and subcutaneous lymphangitis as complication of excessive sexual intercourse of a 44-year-old man. Sexual transmitted diseases could be excluded. Lesions healed up completely under abscess drainage, antibiotic, and anti-inflammatory medication. Conclusion. Previous reports in the literature include several entities of the penile Mondor's disease. Our patient is very unusual in that he presented with a secondary preputial abscess formation due to superficial thrombophlebitis, subcutaneous lymphangitis, and local bacterial colonisation. Abscess drainage plus antiphlogistic and antibiotic medication is the treatment of choice.